Strategi Penerapan Teknologi Digital Berbasis E-Commerce Untuk Meningkatkan Daya Saing UMKM di Industri Kreatif Indonesia - Adinda Putri Aulia; Betty Silfia Ayu Utami (Jurnal Ekonomi dan Bisnis Digital, 2025)
The aim of this research is to analyze strategies for implementing e-commerce-based digital technology to increase the competitiveness of Indonesian creative industry MSMEs. This research uses a qualitative approach to collect data through in-depth interviews, observation and documentation of creative sector MSME stakeholders. The findings show that e-commerce adoption provides significant opportunities for MSMEs to increase product awareness, expand markets, and compete with large companies. However, the biggest challenge is a lack of understanding in managing and optimizing e-commerce platforms and low digital literacy, especially among older MSMEs. Leveraging analytical data from e-commerce platforms allows MSMEs to understand market trends and consumer preferences, but optimizing the use of these features requires ongoing training. Apart from that, digital collaboration with logistics service providers and influencers has also proven successful in increasing operational efficiency and expanding product marketing. Barriers such as uneven digital infrastructure, slow internet access, and limited funds to invest in technology still exist. Therefore, steps are urgently needed to encourage investment in digital infrastructure and digital skills training programs to increase the competitiveness of MSMEs. This study contributes to understanding the role of e-commerce-based digital technology as a strategy to increase the competitiveness of MSMEs in Indonesia's creative economy.